Frontiers in aging - Frontiers Research Foundation (Frontiers Research Foundation, 2020)
Frontiers in Aging is an Open Access journal which publishes rigorously peer-reviewed research that contributes to our understanding of the biological mechanism of aging. We also welcome submissions that explore the fundamental link between mechanisms of aging and age-related diseases. Our focus is on human aging, ultimately aiming to improve healthspan in humans; studies on the development of interventions to improve health and quality of life in humans as we age are also welcomed. We are also interested in insights on aging from model organisms that serve to shed light on general aging mechanisms that affect humans.
Keywords: Aging : Periodicals; Aging